Liebe, Freiheit, Alles - Buetti, Daniele; Kunsthaus, Essen (Essen Münster : Kunstakademie Münster Kunsthaus Essen, 2007)
Bätge, Maria ; Botho Goldbach, Clemens ; Enste, Jan ; Gröning, Julia ; Gudra, Stephanie ; Hajredini, Driton ; Hesse, Katrin ; Hlali, Barbara ; Hohnke, Jonas ; Jie Li ; Kern, Philipp ; Keuck, Lioba ; Kitaigorodsky, Anna ; Koger, Nathalie ; Kottmann, Katja ; Marcin, Nadja Verena ; Müller, Paula ; Nemitz, Friederike ; Neuhaus, Daniela ; Sachs, Rosanna
Biog. p. 122-126
Buch anlässlich der Ausstellung 'Liebe, Freiheit, Alles' im Kunsthaus in Essen, 08.06.2007-05.08.2007
boek